The Influence of Application Quality and Trust on Satisfaction and Repurchase Intention of Traveloka Consumers - Diah Yulisetiarini; Rasikh Hardilegawa Catureswara; Kristian Suhartadi Widi Nugraha; Susanti Prasetiyangtyas; Nadifa Diendara; Azimatul Mauna (Budapest International Research and Critics University, 2023)
This study aims to analyze and examine the effect of application quality and trust on the satisfaction and repurchase intention of Traveloka consumers. There are taken into consideration by Traveloka in determining strategies to maintain consumer repurchase intention through satisfaction by increasing application quality and trust in the future. Further research is expected to add other variables, such as brand image, price, sales promotion, and so forth. This research design employs an explanatory research design. The population in this study involves all Traveloka consumers. The sampling technique applied non-probability sampling with a purposive sampling method. The sample was obtained from 140 respondents with the criteria of consumers who have made a purchase on the Traveloka application more than once in a year and are 16 years old or have an ID card. This study uses quantitative data. The source of data is primary data. Methods of data collection using a questionnaire via a google form. The analytical method used is path analysis. The results show that: Application quality and trust has a significant effect on satisfaction, application quality and trust has a significant effect on repurchase intention, satisfaction has a significant effect on repurchase intention.